Weaving a future : tourism, cloth & culture on an Andean island - Zorn, Elayne (UPCC book collections on Project MUSE., 2004)
The people of Taquile Island on the Peruvian side of beautiful Lake Titicaca, the highest navigable lake in the Americas, are renowned for the hand-woven textiles that they both wear and sell to outsiders. One thousand seven hundred Quechua-speaking peasant farmers, who depend on potatoes and the fish from the lake, host the forty thousand tourists who visit their island each year. Yet only twenty-five years ago, few tourists had even heard of Taquile. In Weaving a Future: Tourism, Cloth, and Culture on an Andean Island, Elayne Zorn documents the remarkable transformation of the isolated rock.